2021
DOI: 10.1016/j.cnp.2021.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Auditory brainstem responses in adults with autism spectrum disorder

Abstract: Highlights Click-evoked auditory brainstem responses were obtained from adults with autism spectrum disorder (ASD) and neurotypical adults. Significantly short peak latencies associated with the auditory peripheral functions of the ASD adults was found compared with the NT adults in the horizontal electrode montage. Adults with ASD may have the abnormalities of processing more in the peripheral auditory system than in the brainstem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…A recent study looking at newborns later diagnosed with ASD at the age of 3–5 years showed ABR latency delays (Delgado et al 2021 ), suggesting the emergence of differences in acoustic processing, at the brainstem level, right after birth. A more recent study tested adults with ASD and found no differences in absolute ABR wave latencies (Fujihira et al 2021 ). The authors showed a shorter summating potential (SP), suggesting normal auditory processing in the brainstem for ASD adults (Fujihira et al 2021 ).…”
Section: Results and Critical Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study looking at newborns later diagnosed with ASD at the age of 3–5 years showed ABR latency delays (Delgado et al 2021 ), suggesting the emergence of differences in acoustic processing, at the brainstem level, right after birth. A more recent study tested adults with ASD and found no differences in absolute ABR wave latencies (Fujihira et al 2021 ). The authors showed a shorter summating potential (SP), suggesting normal auditory processing in the brainstem for ASD adults (Fujihira et al 2021 ).…”
Section: Results and Critical Discussionmentioning
confidence: 99%
“…A more recent study tested adults with ASD and found no differences in absolute ABR wave latencies (Fujihira et al 2021 ). The authors showed a shorter summating potential (SP), suggesting normal auditory processing in the brainstem for ASD adults (Fujihira et al 2021 ).…”
Section: Results and Critical Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While ABRs have been used extensively to assess auditory brainstem physiology 17 and its abnormalities 18,19 , the capacity of ABRs to be modulated by pharmacological agents remains poorly understood. Therefore, we set out to test the effects of a wide range of pharmacological modulators on rodent ABRs.…”
Section: Introductionmentioning
confidence: 99%